Characteristics of Goat Ovarium Granulosa Cells With Extract Leaves ‎‎(Schleichera oleosa) at Different Passage Levels in Vitro - Hanifah, Lil; Muti’ah, Roihatul (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2020)
S. oleosa belongs to the Sapindaceae family and has phytochemicals phenolic acid so that it has enormous benefits in the process antioxidant. The presence of antioxidant activity in cells can affect the defense of the cell protein membrane, so that the ability of cells to perform division is optimal. In vitro this is mostly done by adding hormones to cell culture media or natural compounds to increase cell proliferation. Every population of cell that has undergone division during the proliferation process to confluent is an indication that the cell is aging. This study was an experimental study was designed using a completely randomized design (CRD) with 5 treatments and 5 replications as follows: K0: granulose cells and culture media without treatment (0 µl), P1: granulose cells and culture media with 1% kesambi leaf extract. (30 µl), P2: granulose cells and culture media given kesambi leaf extract 1.5% (45 µl), P3: granulose cells and culture media given kesambi leaf extract 2% (60 µl) and P4: granulosa cells and The culture media was given 2.5% (75 µl) to the leaves extract., the characteristics of goat ovarian granulosa cells by giving kesambi (Scheichera oleosa) leaf extract at different passages were at the level of confluence showing the highest value in passage I, namely treatment P1. Meanwhile, the level of viability shows the highest value in section I, namely the P4 treatment